New Trends in the Methodologies of Determination of Benzodiazepine Residues in Biological Samples - Israel S. Ibarra; Isaí Vázquez-Garrido; Gabriela Islas; Juan F. Flores-Aguilar (Separations)
The benzodiazepines are essential drugs used in medicine for anxiolytic, sedative, and hypnotic effects. According to the World Health Organization, the benzodiazepines are the most prescribed hypnotic drugs in the last decade (2010 at time), and their inappropriate use can damage the environment and human health. The availability of efficient analytical methods is crucial for the determination of these drugs in a complex matrix such as biological samples in clinical settings. In the last decade, several methods have been developed and have been applied to the detection and determination of benzodiazepines or their derivates. The present manuscript reviews selective and sensitive methodologies based on chromatographic, electrophoretic, and electrochemical systems for the determination of benzodiazepines in biological samples, covering the time of the last years and providing detailed information on sample pretreatment and instrumental conditions.